P253 NVA237 once daily offers rapid and clinically meaningful bronchodilation in COPD patients that is maintained for 24 h: the GLOW1 trial. (2nd December 2011) - D'Urzo, T; Ferguson, G; Martin, C; Alagappan, V K T; Banerji, D; Lu, Y; Horton, R; Overend, T
Abstract : Introduction: NVA237 (glycopyrronium bromide) is an inhaled long-acting muscarinic antagonist (LAMA) in development for the once-daily (qd) treatment of COPD. The GLOW1 study evaluated the efficacy and safety of NVA237 in patients with moderate-to-severe COPD. Methods: Patients were randomised (2:1) to 26 weeks double-blind treatment with NVA237 50 μg qd or placebo (PBO). Study drugs were administered via a single-dose dry powder inhaler (Breezhaler ® device). Primary efficacy endpoint: trough FEV1 (mean of 23 h 15 min and 23 h 45 min post-dose values) vs PBO after 12 weeks. Results: 822 patients were randomised; mean age was 63.9 years, mean post-bronchodilator FEV1 was 55% predicted. 80.5% completed the study. At Week 12 there was a statistically significant and clinically relevant difference between NVA237 vs PBO in mean trough FEV1 (108 ml; p<0.001). Trough FEV1 was also significantly higher at Day 1 and Week 26 (treatment difference: 105 ml and 113 ml, respectively; p<0.001). Serial spirometry in a subpopulation of patients showed statistically superior (p<0.001) and clinically meaningful improvements in FEV1 with NVA237 vs PBO at all timepoints on Day 1, Week 12 and Week 26. NVA237 had a rapid onset of action with an increased FEV1 of 93 ml at 5 min and 144 ml at 15 min vs PBO after the first dose on Day 1 (p<0.001). Overall, the incidence of adverse events (AEs) was similar between treatment groups (NVA237: 57.5%; PBO: 65.2%). Serious AEs were reported by 7.5% of NVA237- vs 9.0% of PBO-treated patients. Conclusion: NVA237 50 μg once daily was generally safe and well tolerated. Improvements in bronchodilation were rapid, clinically meaningful and maintained for 24 h throughout the study.